Feeding practices among tribal mothers of malnutrition prevalent region of Amravati District in India - Mahure, Pankaj; Gurjar, Yashashree; Sawkar, Jitendra (Indian Journal of Child Health, 2017)
Introduction: Due to lack of intra- and post-natal care, the feeding practices can lead to a number of morbidities in the infancy period. Infant care in the community is influenced by cultural practices prevalent in the specific area apart from medical and economic reasons. Objectives: The objectives of this study were to understand prevalent feeding practices among tribal mothers having children